Song plasticity over time and vocal learning in clay-colored thrushes - Vargas Castro, Luis Esteban (2015)
Songbirds have been traditionally classified into close-ended or open-ended learning species according to the length of the sensitive period during which birds are able to memorize new vocalizations. Closed-ended learners are generally not capable of changing their song after the first year of life, while open-ended learners show song plasticity as adults. A few Turdus species have been sug- gested to be open-ended learners, but no long-term study has been conducted to investigate their song plasticity over time. We analyzed the songs of clay-colored thrushes, T. grayi, over four successive breeding seasons to assess song plasticity in their syllable repertoires within and between breeding seasons. A total of 16,262 syllables were classi- fied through visual inspection of spectrograms and multi- dimensional scaling analysis based on spectrogram correlations. On average, 563 ± 153 (SD) syllables per male per breeding season were analyzed. Male repertoire size was 9–20 syllable types. Males were capable of modifying their syllable repertoire between the initial and final periods of the breeding season. Song plasticity within breeding seasons may be associated with imitation between neighboring males, suggesting song learning in males that were C2 years old. This short-term plasticity is not enough, however, to explain the high proportion of change (mean = 65 % syllable types) in repertoire composition between breeding seasons in adult males. Song plasticity resulting from annual changes in repertoire composition could be explained by open-ended learning, but another mechanism, extended memory and re-expression, could also explain long-term plasticity. Experimental studies controlling the acoustic environment are needed to determine which mechanism is responsible for such a high level of song plasticity.